EKSPOR VANILI DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Anggraeni, Iis; Nurhadi, Eko; Widayanti, Sri (Berkala Ilmiah AGRIDEVINA, 2019)
The purpose of this study is to analyze the factors that affect the export of Vanilla Indonesia and the influence of Vanilla Indonesia's exports to Indonesia's economic growth. The research method used SPSS by using Multiple Linier Regression Model. Data collected in this study are secondary data from 1998-2016 from the Central Bureau of Statistics (BPS), Directorate General of Estate Crops, Bank Indonesia, Ministry of Trade and other sources. The results showed that the nominal exchange rate (exchange rate of Rupiah to Dollar) and Export Price (FOB) gave insignificant influence to the export of Vanilla Indonesia, the production and consumption of Vanilla in the country gave a significant and positive influence to the export volume of Vanilla Indonesia. Vanilla export volumes have no significant and significant effect on Indonesia's economic growth and export volume Rubber positively affects economic growth in Indonesia. DOI : https://doi.org/10.33005/adv.v8i2.1802